1,5-Dimethyl-3-propargyl-1H-1,5-benzodiazepine-2,4(3H,5H)-dione - Dardouri, R.; Chahdi, F.O.; Saffon, N.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, C(14)H(14)N(2)O(2), comprises two independent molecules, which slightly differ in the orientation of the propargyl chain. In both molecules, the diazepine ring adopts a boat conformation with the propargyl-bearing C atom as the prow and the C atoms at the ring junction as the stern. The carbonyl O atom of one independent molecule is hydrogen bonded to the acetylenic H atom of the other independent molecule. In the crystal, symmetry-related molecules are linked together by C-H center dot center dot center dot O hydrogen bonds, forming a ribbon-like structure along the c axis.